2021
DOI: 10.1177/0885066620984443
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Prothrombin Complex Concentrate and Recombinant Activated Factor VII for the Management of Bleeding With Cardiac Surgery

Abstract: Bleeding following cardiac surgery that warrants transfusion of blood products is associated with significant complications, including increased mortality at 1 year following surgery. Factor concentrates, such as prothrombin complex concentrate (PCC), or recombinant activated factor VII (rFVIIa) have been used off-label for bleeding in cardiac surgery that is refractory to conventional therapy. The objective of this retrospective study is to assess the hemostatic effectiveness of 4-factor PCC or rFVIIa for ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…More recently, we have learned low-doses of 4-factor PCC may be sufficient; a 2021 study found low-dose rFVIIa (2 mg or 20 mcg/kg) and low-dose 4-factor PCC (1000 units or 15 units/kg) were equally safe and effective for refractory bleeding in cardiac surgery. 32 In the absence of a 4-factor PCC dosing protocol, there is potential for administration of larger than necessary doses (e.g., 2,172 units/patient pre-protocol and 4,284 units/patient post-protocol in our 15 study). Therefore, if restricting rFVIIa off-label use, it seems critical to also standardize use and dosing of both PCC and rFVIIa to avoid shifts in prescribing or overutilization of PCC.…”
Section: Discussionmentioning
confidence: 89%
“…More recently, we have learned low-doses of 4-factor PCC may be sufficient; a 2021 study found low-dose rFVIIa (2 mg or 20 mcg/kg) and low-dose 4-factor PCC (1000 units or 15 units/kg) were equally safe and effective for refractory bleeding in cardiac surgery. 32 In the absence of a 4-factor PCC dosing protocol, there is potential for administration of larger than necessary doses (e.g., 2,172 units/patient pre-protocol and 4,284 units/patient post-protocol in our 15 study). Therefore, if restricting rFVIIa off-label use, it seems critical to also standardize use and dosing of both PCC and rFVIIa to avoid shifts in prescribing or overutilization of PCC.…”
Section: Discussionmentioning
confidence: 89%
“…While the design of this study did not compare patients who received 4F-PCC to those who did not, the reported chest tube output and blood product transfusion in the postoperative setting are less than those reported in other pediatric cardiac surgery studies. 21 22 23 24 25 27 28 29 30 31…”
Section: Discussionmentioning
confidence: 99%
“…While the design of this study did not compare patients who received 4F-PCC to those who did not, the reported chest tube output and blood product transfusion in the postoperative setting are less than those reported in other pediatric cardiac surgery studies. [21][22][23][24][25][27][28][29][30][31] Bleeding is a common issue in pediatric patients undergoing cardiac surgery requiring CPB, and the lack of standard guidelines often results in utilization of a wide variety of blood products. Mechanisms contributing to excessive bleeding following CPB include heparinization, hemodilution through circuit prime, hypothermia, as well as interactions between the coagulation and inflammatory systems.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosis rates were higher in the recombinant factor VIIa versus the 4-factor PCC groups, but the differences were not statistically significant (10 vs. 3.6%, P ¼ 0.159; 26 vs. 13%, P ¼ 0.08.) [14,15] 4-factor PCC is less expensive. The cost of 4-factor PCC is $ 3.41 per unit, whereas the cost of recombinant factor VIIa is $2.98/mg [16].…”
Section: Discussionmentioning
confidence: 99%